Ultrastructural Studies on the Magnum of Oviduct in Emu (Dromaius novaehollandiae) - Naik, Raghu (Indian Journal of Veterinary Anatomy, 2020)
The ultrastructure of magnum was studied in eight adult apparently healthy emu birds. Mucosa contained different folds, of which the primary folds were more prominent. Several tubular invaginations on the primary folds and the openings of the proprial glands appeared on the surface epithelium. The magnum contained ciliated and non ciliated columnar cells, goblet cell of which non ciliated columnar cells and goblet cells were predominant. Two columnar cell types were observed in the surface epithelium i.e. light secretary cells and dark non secretary cells. . Prominent elongated mitochondria were concentrated in the sub apical region.Three basic cells were observed in the basal part of tubular glands viz., type A cells packed with strongly electron dense granules, type B cells filled with amorphous material of low electron density.